Umm-el-Breigât (Tebtynis): campagna di scavo 2020 (ACME, 2023)
In 2020, the French and Italian mission of Milan University and Cairo Institut français d’archéologie orientale (Ifao) worked in the ruins of ancient Tebtynis from September 15th to November 7th. The excavations were extended in the southern sector of the village along the large street called in demotic papyri “dromos of Tefresudj(ty?)”. Two tower-houses built in the 2nd and 1st century BC were unearthed, many buildings dating from the Ptolemaic and Roman period were excavated and a square was discovered. Although the area was partly disturbed, many objects and texts were collected.